Penanganan Perkara Tindak Pidana Hak Cipta Lagu oleh Penyidik Pegawai Negeri Sipil di Kantor Wilayah Kementerian Hukum Jawa Barat (International Forum of Researchers and Lecturers, 2026)
The rapid development of digital technology has increased the risk of song copyright infringement, thereby requiring effective and adaptive law enforcement mechanisms. Song copyright, as part of intellectual property rights, is protected under Law Number 28 of 2014 on Copyright, with certain infringements classified as complaint-based criminal offenses. This study aims to analyze the handling of criminal cases of song copyright infringement by Civil Servant Investigators at the Regional Office of the Ministry of Law in West Java and to evaluate the effectiveness of their enforcement practices. The research employs a normative-empirical method with a descriptive-analytical approach, combining statutory analysis with empirical data obtained through interviews and field observations. The findings reveal that case handling is conducted through structured stages, including complaint submission, preliminary examination, mediation, and follow-up actions. Mediation constitutes the primary mechanism for dispute resolution, reflecting the application of the ultimum remedium principle and a restorative justice approach. Although the procedural framework has been implemented in accordance with applicable regulations, enforcement effectiveness remains constrained by limited human resources, budgetary limitations, insufficient technical capacity, low public legal awareness, and inadequate inter-agency coordination. These results underscore the importance of strengthening institutional capacity and enhancing enforcement effectiveness to ensure sustainable protection of song copyright.